Sources and Cycling of Particulate Organic Matter in Baffin Bay: A Multi-Isotope δ13C, δ15N, and Δ14C Approach - Fox, Aislinn; Walker, Brett D. (Frontiers in Marine Science, 2022)
The Canadian Arctic is warming at three times faster than the rest of the planet. The impact of global climate change on the Arctic carbon cycle is poorly constrained. In particular, few data exist which examine carbon cycling in Baffin Bay. Sinking particulate organic matter (POMsink) is a key component of the biological carbon pump (BGC) and provides a direct linkage between surface productivity and the preservation of carbon in marine sediments. While POMsink provides a rapid POM shunt to the deep ocean (days) the majority of marine POM is suspended (POMsusp) persists for years in the water column. Stable carbon (δ13C), nitrogen (δ15N) and radiocarbon (Δ14C) isotopic measurements are powerful tools for evaluating sources and cycling of POM. In this study, we measure depth-integrated (0-400m) POMsusp stable carbon (δ13C), nitrogen (δ15N) and radiocarbon (Δ14C) values at 11 stations in Baffin Bay. We employ a novel %biomass proxy and C:Na ratios to evaluate the diagenetic state of POM. POMsusp δ13C and δ15N values ranged from −21.6‰ to −29.5‰, and +3.84‰ to +7.21‰, respectively. POMsusp Δ14C values ranged from −41.8‰ to +76.8‰. Together, our results suggest Baffin Bay POMsusp has multiple carbon and nitrogen sources with variable diagenetic states. POMsusp δ13C and Δ14C are strongly correlated to surface salinity, indicating a strong influence of water mass sources on POMsusp isotopic composition and 14C-age. POMsusp from coastal Greenland stations have similar 14C values to surface dissolved inorganic carbon (DIC) and high Chl-a biomass, consistent with primary production as the predominant POMsusp source. Positive POMsusp Δ14C values in central Baffin Bay suggest an accumulation of atmospheric “bomb” 14C in the sub-polar gyre. POMsusp exiting Davis straight via the Baffin Island current was determined to have a significant degraded, resuspended sediment component. Finally, POMsusp δ15N values highlight two distinct N sources in Baffin Bay: Pacific and Arctic nutrients at Northern gateway stations vs. the influx of Atlantic nutrients via the Davis Strait along coastal Greenland. Overall, these first Baffin Bay POMsusp Δ14C values provide useful baseline data for rapidly changing Arctic ecosystem.